The history and politics of voting technology chads and other scandals - Saltman, Roy G. (Palgrave Macmillan, 2008)
Saltman traces the evolution of voting technology in the USA, from voice to digital, highlighting how the antiquated systems in use today are a legacy of the industrial revolution of the Nineteenth-century and the early computer revolution of the 1950s and analyses the current day situation